Village Funds and Rural Poverty Reduction in Samosir Regency: Evidence from 2019–2024 Policy Implementation - Novita Sinaga; Irsad Lubis (Law and Economics, 2026)
Poverty in Samosir Regency is still the main problem even though the Village Fund policy has been implemented as an instrument of village development. This study aims to analyze the effectiveness of the Village Fund in poverty alleviation during the 2019–2024 period. The method used is a descriptive-analytical qualitative approach with secondary data from the Central Statistics Agency, policy documents, and local government reports, which are analyzed using the Miles and Huberman model. The results of the study show that the poverty rate fluctuated from 12.52% (2019) to 13.10% (2021) due to the pandemic, then decreased to 11.63% (2024), but tended to stagnate in the final period. The allocation of Village Funds increased from IDR 95 billion (2019) to IDR 115 billion (2024), with a shift in the use of infrastructure (70%) to community empowerment (40%) and a decrease in the portion of BLT from 35% (2021) to 10% (2024). Supporting indicators also show improvements, such as a decrease in unemployment from 4.8% (2021) to 3.4% (2024), an increase in the average length of school from 8.5 to 9.0 years, and access to infrastructure from 65% to 78%. However, these improvements have not had a significant impact on poverty reduction. Thus, the effectiveness of the Village Fund is still not optimal and requires policies that are more oriented towards economic empowerment and strengthening the capacity of village communities.